Citedness Buletin Pengabdian: Bulletin of Community Services (Bull. Community Serv.) in Scopus - Pengabdian, Buletin (Universitas Syiah Kuala, 2021)
Citedness Buletin Pengabdian: Bulletin of Community Services (Bull. Community Serv.) in Scopus